Español - Cruz Basantes, Blanca Herminia (2022)
Introduction. Anaphylaxis is a severe and life-threatening allergic reaction that can cause multi-organ failure and even death. Objectives. Determine the best and most up-to-date management of anaphylaxis in pediatrics. Methodology. In the search for information, the most relevant information with the best scientific support was used in an orderly manner, using the PICO format as a clinical question, and scientific virtual libraries such as: Pub Med, ACCESSSS, Medline, EBSCO and Cochrane were consulted. In addition, scientific information search engines such as UptoDate and DynaMed, on the management of anaphylaxis in pediatrics. Results. 54 scientific articles were found and after analyzing them, 49 were chosen that meet the criteria set forth for this work. Discussion. Anaphylaxis is a life-threatening disorder triggered by a severe allergic reaction. Epinephrine administered intramuscularly is the first line and most effective treatment in the management of this pathology. Conclusions. Early recognition of clinical symptoms is essential for the immediate start of treatment, delaying treatment increases morbidity and mortality due to anaphylaxis and timely treatment of anaphylaxis in pediatrics reduce the probable complications that may occur.